Mind the Gap: A Systematic Review of Research on Restorative Practices in Schools. Issue 2 (3rd July 2021) - Zakszeski, Brittany; Rutherford, Laura
Abstract: Restorative justice approaches in schools have gained popularity given their potential to build safer and more positive school communities, offer alternatives to exclusionary discipline, and promote equity in school outcomes. Historically, research in this area has been lacking, but recent increases in publications point to the need for research syntheses. A systematic literature review was undertaken to describe the state of the literature on restorative practices in schools. Review findings indicate shortcomings of current research in informing practice and the likelihood of a sustained "practice-to-research" gap. Results point to the need for future research to precisely define and describe discrete practices of a restorative justice approach, strategically support and measure practice implementation, and prioritize rigorous experimental evaluations. Practitioners are charged with weighing available empirical evidence with school factors and needs in adopting evidence-based practices to cultivate safer and more supportive schools. Impact Statement Schools' adoption of restorative justice approaches has outpaced research in this area. Existing research on restorative practices has profound limitations, which researchers must address to guide practice and address the needs of schools. Practitioners must stay current on this evolving literature base to identify evidence-based practices to integrate within a multi-tiered systems of support framework.